The Effectiveness of the Radec Learning Model Assisted by Wordwall Media on Critical Reading Skills - Kenya Ziva Mahendra; Dede Permana; Eva Astuti Mulyani (Raja Zulkarnain Education Foundation, 2026)
This study aims to determine the effectiveness of the RADEC (Read, Answer, Discuss, Explain, Create) learning model assisted by Wordwall media on the critical reading skills of fourth-grade students. The research was conducted at SDN 122 Pekanbaru during the even semester of the 2025/2026 academic year. The research population included all fourth-grade students at SDN 122 Pekanbaru, with a sample of 44 students consisting of class IV.A (22 students) as the experimental group and class IV.B (22 students) as the control group, determined using a purposive sampling technique. The research instrument was a critical reading ability test in the form of validated essay questions. Data analysis tools included prerequisite tests (normality and homogeneity tests), hypothesis testing using the Independent Samples T-Test, and the N-Gain test to measure the level of effectiveness. The results showed a significant influence of the RADEC model assisted by Wordwall media, evidenced by a Sig. (2-tailed) value of 0.010 < 0.05. The effectiveness level in the experimental group showed an average N-Gain of 0.3039, categorized as moderate, while the control group reached 0.2010, categorized as low. Thus, it can be concluded that the RADEC learning model assisted by Wordwall media is effective in improving the critical reading skills of fourth-grade students at SDN 122 Pekanbaru.